2021
DOI: 10.1021/acsmacrolett.0c00829
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Centrifugal Multispinning Production of Polymer Micro- and Nanofibers for Mask Filter Application with a Potential of Cospinning Mixed Multicomponent Fibers

Abstract: Recently, the polymer nanofiber web is in high demand as a strong barrier against harmful particles due to its high capture efficiency and strong droplet-blocking ability. As an advanced spinning technique, the centrifugal multispinning system was designed by sectioning a rotating disk into triple subdisks, showing mass producibility of polymer nanofibers with cospinning ability. Using the system, gram-scale production of polystyrene (PS), poly(methyl methacrylate), and polyvinylpyrrolidone (PVP) was demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Centrifugal force spinning (CFS) has fast emerged as a method for producing continuous fibers or filaments from polymer solutions and melts, often with additives that enhance the functionality of resulting nonwoven structures. Cotton candy as a product highlights the ease, rate, flexibility, and allure of this fiber/nonwoven manufacturing process and its scalability. Many recent studies focus on centrifugal spinning polymer solutions to take advantage of room-temperature processing and the possibility of producing finer fibers without the need for superfine nozzles, melt-processable polymers, and methods like electrospinning that require high-voltage sources and work with a limited range of solvents. ,,, However, a combination of complex free surface flow and instabilities, non-Newtonian fluid properties that change due to evaporation or solidification, mass or heat transfer (often both), as well as polymer stretching, orientation, and crystallization accompany the formation of centrifugally spun fibers. The coupling of multiple transport processes and non-Newtonian fluid mechanics present formidable challenges to creating a CFS processability map and connecting spinnability, heuristically identified with the ability to make fibers, with the choices of process and material parameters. Several theoretical and simulation studies probe the influence of non-Newtonian rheology and fluid mechanics in dictating the initiation, extension, and thinning of the spiraling jet from a fast-rotating spinneret or nozzle, the role of viscoelastic free surface flows and instabilities, and the influence of evaporation or solidification process. The significant impacts of process parameters like spinning speed, nozzle shape and size, distance to the collector and airflow, and varying polymer concentration and molecular weight on fiber diameter and morphology are tabulated and discussed in several experimental and theoretical studies. , , However, fundamental questions remain about the impact of solvent choice, through the influence on rheological response, especially to extensional flows and evaporation, in dictating spinnability, motivating this study.…”
Section: Introductionmentioning
confidence: 99%
“…Centrifugal force spinning (CFS) has fast emerged as a method for producing continuous fibers or filaments from polymer solutions and melts, often with additives that enhance the functionality of resulting nonwoven structures. Cotton candy as a product highlights the ease, rate, flexibility, and allure of this fiber/nonwoven manufacturing process and its scalability. Many recent studies focus on centrifugal spinning polymer solutions to take advantage of room-temperature processing and the possibility of producing finer fibers without the need for superfine nozzles, melt-processable polymers, and methods like electrospinning that require high-voltage sources and work with a limited range of solvents. ,,, However, a combination of complex free surface flow and instabilities, non-Newtonian fluid properties that change due to evaporation or solidification, mass or heat transfer (often both), as well as polymer stretching, orientation, and crystallization accompany the formation of centrifugally spun fibers. The coupling of multiple transport processes and non-Newtonian fluid mechanics present formidable challenges to creating a CFS processability map and connecting spinnability, heuristically identified with the ability to make fibers, with the choices of process and material parameters. Several theoretical and simulation studies probe the influence of non-Newtonian rheology and fluid mechanics in dictating the initiation, extension, and thinning of the spiraling jet from a fast-rotating spinneret or nozzle, the role of viscoelastic free surface flows and instabilities, and the influence of evaporation or solidification process. The significant impacts of process parameters like spinning speed, nozzle shape and size, distance to the collector and airflow, and varying polymer concentration and molecular weight on fiber diameter and morphology are tabulated and discussed in several experimental and theoretical studies. , , However, fundamental questions remain about the impact of solvent choice, through the influence on rheological response, especially to extensional flows and evaporation, in dictating spinnability, motivating this study.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have also been made to improve the ltration efficiency of masks by reducing the diameter of lter bers, increasing the affinity between particles and lter fabrics, optimizing the ber structure to form groove structures on the surface to trap more ultrane particles, etc. [111][112][113][114] The degree of t between the mask and wearer also affects the ltration and protection performance of the mask since it was indicated that the gaps between the mask and wearer could lead to over 60% decline of ltration efficiency. 10 Notably, 3D printing technology could act as a replenishment in the early shortage of masks and help to customize individual-tting face seal masks and respirators.…”
Section: Improvement Of Mask Performancementioning
confidence: 99%
“…For instance, researchers are developing methods that can resolve scalability problems by redesigning the fabrication platforms with parallel fiber production and improving organization by templated polymerization. [3,[29][30][31] Still, the larger scale adoption of such techniques and their capabilities are limited. Thus, it is essential to focus research efforts on development of new and more versatile methods for making complex polymeric morphologies.…”
Section: Introductionmentioning
confidence: 99%